LncRNA SNHG7/miR-34a-5p/SYVN1 axis plays a vital role in proliferation, apoptosis and autophagy in osteoarthritis - Feng Tian; Junhu Wang; Zhanhua Zhang; Jie Yang (Biological Research, 2020)
Abstract Background Osteoarthritis (OA) is one of the most common rheumatic diseases of which clinical symptoms includes swelling, synovitis and inflammatory pain, affect patients’ daily life. It was reported that non-coding RNAs play vital roles in OA. However, the regulation mechanism of ncRNA in OA pathogenesis has not been fully elucidated. Methods The expression of SNHG7, miR-34a-5p and SYVN1 was detected using qRT-PCR in tissues, serum and cells. The protein expression of SYVN1, PCNA, cleavage-caspase 3, beclin1 and LC3 were measured using western blot. The RNA immunoprecipitation (RIP), RNA pulldown, and luciferase reporter assays were used to verify the relationship between SNHG7, miR-34a-5p and SYVN1. The MTT and flow cytometry assay was performed to detected cell proliferation and cell apoptosis respectively. Results In this study, SNHG7 and SYVN1 expression were down-regulated, but miR-34a-5p was up-regulated in OA tissues and IL-1β treated cells compared with normal tissues and chondrocyte. Functional investigation revealed that up-regulated SNHG7 or down-regulated miR-34a-5p could promote cell proliferation and inhibit cell apoptosis and autophagy in OA cells. More than that, RIP, pulldown and luciferase reporter assay was applied to determine that miR-34a-5p was a target miRNA of SNHG7 and SYVN1 was a target mRNA of miR-34-5p. Rescue experiments showed that overexpression of miR-34a reversed high expression of SNHG7-mediated suppression of apoptosis and autophagy as well as promotion of proliferation, while its knockdown inhibited cell apoptosis and autophagy and promoted cell proliferation which could be impaired by silencing SYVN1. In addition, SNHG7 regulated SYVN1 through sponging miR-34a-5p. Conclusion SNHG7 sponged miR-34a-5p to affect cell proliferation, apoptosis and autophagy through targeting SYVN1 which provides a novel sight into the pathogenesis of OA.